Teaching English for Specific Purposes at Vocational Institution: Teachers’ Beliefs, Practices and Challenges - Sabarniati, Sabarniati; Fitriani, Naria; Kurniawati, Kurniawati (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
The intention of this study is to conceive teachers’ reflections regarding their experiences of teaching English for Specific Purpose (ESP) at Politeknik Aceh. Their convictions, practices as well as challenges were scrutinized in order to figure out better implementation for ESP classes in the future. Three ESP teachers were interviewed besides observing their classroom and analyzing their syllabus design. They agree that ESP is a compulsory subject in vocational institutions. The students need to prepare themselves for work life ahead, because beside communicating with local people, they surely will interact and communicate with the people from other countries globally. The syllabus was designed by the teachers adapting with the students’ need and industrial growth. They constantly revise and upgrade their syllabus and teaching materials depending on current situation of the students and their work targets. The teachers encountered similar challenge in their experiences of teaching ESP, that they have to deepen their insights regarding the field of the study being taught. Surprisingly, they even exchange knowledge with the students, for example; the teachers learnt about electrical from the students whilst teaching ESP for electrical engineering students. Moreover, the most challenging tendency in teaching ESP at Politeknik Aceh is the requirement of deep understanding of industry-specific terminology and concepts. So, it is essential to regularly update materials to reflect industry advancements, incorporate more authentic and current resources, and provide professional development opportunities for ESP teachers.